IMPROVING THE WELFARE OF MICRO, SMALL, AND MEDIUM ENTERPRISES (MSMEs) AFFECTED BY ECONOMIC CHANGE THROUGH A COMMUNITY ECONOMIC DEVELOPMENT APPROACH IN LAMPUNG PROVINCE - Hanif, Hanif; Susanto, Is; Mukri, Moh. (JURNAL AL-IJTIMAIYYAH, 2024)
The spread of Covid-19 in Indonesia has had wide-ranging impacts on human life, particularly on the economy. Therefore, a breakthrough is needed to address this issue by actively involving the community and working with the government to develop a community economic development program. This background prompted this study intending to obtain the right program for MSMEs affected by Covid-19 in Lampung Province. This study uses a qualitative approach with data collection methods, including observation, interviews, and documentation. The data analysis method used is qualitative analysis, with conclusions drawn using deductive thinking frameworks. The results of this study indicate that the community economic development approach by the Lampung Provincial Government has been implemented using the processes and stages outlined in existing theories. From the process perspective, this approach has successfully gone through each process, and so far, the program is considered capable of addressing the problems faced by MSMEs affected by Covid-19. This approach is considered more effective, as the program has been widely felt and successfully fostered creativity, trust, discipline, optimism, and improving family economies. This approach has also been implemented by Islamic economic values , which consist of the values of divinity, justice, and cooperation.